Speech act analysis of oral presentation of thesis abstracts by Undergraduate EFL thesis defence - Imanuel Kamlasi; Hendi Pratama; Sri Wahyuni; Seful Bahri (English Learning Innovation, 2026)
Speech acts directly influence institutional power in high-stakes academic communication, such as thesis defence. This study explored the types and functions of speech acts in oral presentations during the EFL thesis defence in the setting of Indonesian higher education. It employed a qualitative descriptive approach and a pragmatic analysis framework to investigate the speech acts in the oral presentation using Searle’s (1969) framework. The participants were eight EFL undergraduates of Timor University. Data were collected through observation and recording. The findings showed that candidates strategically used assertive, directive, commissive, and expressive utterances to navigate academic defences. These acts establish epistemic authority, highlight the significance of research, provide recommendations, structure discourse, and emphasise the ceremonial aspect of defences. These results are useful for understanding academic discourse, speech act realisation, and pragmatic competence in EFL academic settings.